China's Capital Controls - Through the Prism of Covered Interest Differentials - Yin-Wong Cheung; Risto Herrala (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study the renminbi (RMB) covered interest differential - an indicator of the effectiveness of capital controls. It is found that the differential is not shrinking over time and, in fact, appears larger after the global financial crisis than before. That is, capital controls in China are still substantial and effective. In addition to exchange rate changes and volatilities, the RMB covered interest differential is affected by credit market tightness indicators. The marginal explanatory power of these macroeconomic factors, however, is small relative to the autoregressive component and the dummy variables that capture changes in China's policy.
Keywords: E44; F31; F32; 330; NDF implied RMB interest rate; capital controls; asymmetric response; macro determinants; credit market tightness